2020
DOI: 10.5271/sjweh.3918
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and health behavior as causes of educational inequalities in self-rated health: an inverse odds weighting approach

Abstract: Working conditions and health behavior as causes of educational inequalities in self-rated health: an inverse odds weighting approach by Schram JLD, Oude Groeniger J, Schuring M, Proper KI, van Oostrom SH, Robroek SJW, Burdorf A The novel causal mediation approach 'inverse odds weighting' showed that working conditions and health behaviors accounted for more than half of the educational inequalities in self-rated health. Preventive interventions focusing on improving working conditions and health behavior amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 43 publications
4
34
1
1
Order By: Relevance
“…The potential of workplace health promotion Unhealthy behaviors (eg, insufficient physical activity, an unhealthy diet, high alcohol intake and smoking) and obesity are risk factors for adverse health outcomes (1,2), productivity loss due to presenteeism or sickness absence (3)(4)(5)(6), and early exit from paid employment (7,8). Poor health and unhealthy behaviors are more prevalent among workers from low socioeconomic positions (1,2,9), as are unemployment and work disability (10,11). With a growing challenge in our societies to work longer, reflected in the increasing statutory retirement age in many European countries, an urgent need exists to enhance workers' health to remain in paid employment.…”
Section: Decades Of Workplace Health Promotion Research: Marginal Gains or A Bright Future Ahead?mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of workplace health promotion Unhealthy behaviors (eg, insufficient physical activity, an unhealthy diet, high alcohol intake and smoking) and obesity are risk factors for adverse health outcomes (1,2), productivity loss due to presenteeism or sickness absence (3)(4)(5)(6), and early exit from paid employment (7,8). Poor health and unhealthy behaviors are more prevalent among workers from low socioeconomic positions (1,2,9), as are unemployment and work disability (10,11). With a growing challenge in our societies to work longer, reflected in the increasing statutory retirement age in many European countries, an urgent need exists to enhance workers' health to remain in paid employment.…”
Section: Decades Of Workplace Health Promotion Research: Marginal Gains or A Bright Future Ahead?mentioning
confidence: 99%
“…Unhealthy behaviors (eg, insufficient physical activity, an unhealthy diet, high alcohol intake and smoking) and obesity are risk factors for adverse health outcomes ( 1 , 2 ), productivity loss due to presenteeism or sickness absence ( 3 6 ), and early exit from paid employment ( 7 , 8 ). Poor health and unhealthy behaviors are more prevalent among workers from low socioeconomic positions ( 1 , 2 , 9 ), as are unemployment and work disability ( 10 , 11 ).…”
Section: The Potential Of Workplace Health Promotionmentioning
confidence: 99%
“…Most of the actions related to improvements in the work context. It has been shown that working conditions contribute as much and sometimes more than healthy behaviors to health of employees with a low SEP [ 38 , 39 ]. Second, participants of the dialogues reported learnings after participating.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the explanatory value of the work-related factors, including both physical and psychosocial demands, was 22%. Several other studies on work ability adjusted for health behaviors and provide evidence that occupational factors impact health outcomes independently of health behavior ( Lund and Csonka, 2003 ; Andersen et al, 2016 ; Schram et al, 2021 ). In an extra analysis of our own dataset, we have added the lifestyle factors smoking, heavy alcohol consumption, obesity, and minutes spent on physical activity (walking, doing a sport) as confounders to our basic analytic model (i.e., model 2 in Table 3 ).…”
Section: Discussionmentioning
confidence: 99%